2005
DOI: 10.1002/adem.200500032
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Elastic Modulus of Laser‐Engineered Composite Boride Coating

Abstract: The effective elastic modulus of a laser‐engineered composite TiB2 coating on AISI 1010 steel substrate has been computed using different micromechanics models and compared with the experimental values. The Hashin‐Shtrikman Bound method evinced most consistent effective elastic modulus values compared to Eshelby and Mori‐Tanaka models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, all of the work on thermal spraying of CNT-reinforced MMCs has been carried out only by our research group. Plasma spraying, [86][87][88][89] HVOF spraying 87,88 and cold spraying 90 have been successfully demonstrated for the fabrication of CNT-reinforced MMC and ceramic coatings. [91][92][93] Laha et al have studied the feasibility of spraying CNTs with Al powders to form composite coatings.…”
Section: Plasma Spraying and High Velocity Oxy-fuel (Hvof) Sprayingmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, all of the work on thermal spraying of CNT-reinforced MMCs has been carried out only by our research group. Plasma spraying, [86][87][88][89] HVOF spraying 87,88 and cold spraying 90 have been successfully demonstrated for the fabrication of CNT-reinforced MMC and ceramic coatings. [91][92][93] Laha et al have studied the feasibility of spraying CNTs with Al powders to form composite coatings.…”
Section: Plasma Spraying and High Velocity Oxy-fuel (Hvof) Sprayingmentioning
confidence: 99%
“…Researchers have tried to incorporate 1-6?5 vol.-%CNTs into a free standing Al-CNT composite structure by the powder metallurgy route 37,63 accompanied by SPS 60 and/or hot deformation. [59][60][61]86,88,145,146,148,158,174 A maximum of 129% increase in the tensile strength has been reported with the addition of 5 vol.-%CNT addition. 60 On the contrary, Salas et al 145 have reported deterioration in hardness in a shock-wave-consolidated Al-5 vol.-%CNT composite.…”
Section: Aluminium-cnt Compositesmentioning
confidence: 99%
“…The bulk elastic modulus of the ultrasonic cast Al 6061 –WS 2 composites was analytically calculated using continuum micromechanics Hashin–Shtrikman lower bound model. [ 35,36 ] This model is appropriate for isotropic composites reinforced by randomly distributed particles, as observed in the present case (Figure 5). According to this model, the elastic modulus of the composite is given byEnormalc=Enormalmfalse{ EnormalmVnormalm+Enormalrfalse(Vnormalr+1false) false}EnormalrVnormalm+Enormalmfalse(Vnormalr+1false)where E (GPa) is the elastic modulus, V is the volume fraction, and the subscripts c, m, and r stand for composite, matrix, and reinforcement, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…The bulk elastic modulus of the ultrasonic cast Al 6061 -WS 2 composites was analytically calculated using continuum micromechanics Hashin-Shtrikman lower bound model. [35,36] This model is appropriate for isotropic composites reinforced by randomly distributed particles, as observed in the present case (Figure 5). According to this model, the elastic modulus of the composite is given by…”
Section: Analytical Continuum Micromechanics Modelsmentioning
confidence: 75%